CRIMINAL LIABILITY FOR FRAUDULENT ENTREPRENEURSHIP - Ravshanov Surat Botir o’g’li (Web of Journals Publishing, 2024)
This article examines the concept of "fake entrepreneurship" and its criminal liability under the law. It also examines the criminal aspects of fraud, including tax evasion, falsification of business activities, and illegal profit-making. It also outlines the forms of fake entrepreneurship, legal mechanisms for their detection, and penalties established by criminal law.
Keywords: Fraudulent entrepreneurship, criminal liability, tax evasion, fraudulent establishment of companies, fraud, economic crimes, business fraud, financial responsibility, entrepreneurial activity, violation of the law, legal liability, financial indicators and the Criminal Code.